Why Firms Hold Cash? An Empirical Investigation of UK Companies - Chen, Shuangying (2010)
This paper examines the determinants of holdings of cash by publicly traded UK firms over the period 2000-2009. Larger firms hold less cash as they have greater access to the capital market. Cash holdings in firms with better investment opportunities and more volatile cash flow are relatively larger. And firms with less liquid asset substitutes tend to hold higher ratios of cash to total assets to ensure the finance of positive-NPV projects. Financially constrained firms that are more sensitive to the idiosyncratic risk increase their cash holdings; but for financially unconstrained firms, cash holdings are irrelevant. In addition, we observe that cash holdings vary across industries. However, there is less evidence that firms hold more cash as they incur large capital expenditures.